Analisis Defect pada Proses Quality Control Packing Bata Ringan Menggunakan Metode Six Sigma pada PT. XYZ - Ariansyah, Muhammad Syakirul; Nugroho, Dony Satriyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Production defects are the main problem in making a product which can reduce production quality. Quality improvement is considered important in improving production quality. This research aims to improve quality by reducing the number of defects that occur on the production floor. This research used a quantitative method research design, and 40 data were taken randomly. Data was collected through direct observation in the field. Data analysis was carried out using the six sigma method and seven tools to determine the type of priority defects. The results of this research show that the six sigma value is still low, namely 2.67, which indicates that improving quality is needed to reduce the number of defects. Improving quality is an important factor in reducing the number of defects that occur. This research provides practical implications for company policy makers in designing strategies to improve production quality and reduce the number of defects.